Alkaline Phosphomonoesterase-Harboring Microorganisms Mediate Soil Phosphorus Transformation With Stand Age in Chinese Pinus massoniana Plantations - Liang, Yueming; Li, Mingjin; Pan, Fujing; Ma, Jiangming; Yang, Zhangqi; Ling, Tianwang; Qin, Jiashuang; Lu, Shaohao; Zhong, Fengyue; Song, Zunrong (Frontiers in Microbiology, 2020)
phoD-harboring microorganisms facilitate mineralization of organic phosphorus (P), while their role in the regulation of soil P turnover under P-limited conditions in Pinus massoniana plantations is poorly understood. The aim of the present study was to investigate the effects of stand age and season on soil P fractions and phoD-harboring microorganism communities in a chronosequence of Chinese P. massoniana plantations including 3, 19, and 58 years. The soil P fractions (i.e., CaCl2-P, citrate-P, enzyme-P, and HCl-P) varied seasonally, with the higher values observed in the rainy season. The concentrations of the fractions were higher in old plantation (OP) soils and lower in young planation (YP) soils in both seasons. The OTU abundances were negatively correlated with total available P concentration, while were positively correlated with ALP activity at at 0-10 cm soil depth. The results indicate that phoD-harboring microorganisms have great potential to mineralize organic P under P-poor conditions, and highlights those microorganisms are indicators of P bioavailability in P. massoniana plantations.